Características dos espermatozóides em espécies de Leptodactylus (Anura, Leptodactylidae) - Salles, Natália Maria Espíndola [UNESP] (2014)
Species in the subfamily Leptodactylinae exhibit a great diversity of reproductive modes and adopt different reproductive strategies, including polyandrous matings. The analysis of the gonad and sperm morphology in a phylogenetic context is crucial to understand the evolution of this alternative reproductive strategy in anurans. Here, we describe the sperm morphology and ultraestructure of 11 Leptodactylus species and that of Lithodytes lineatus and investigated the relationship between gonad and sperm morphology in polyandrous and non polyandrous Leptodactylus species using phylogenetic comparative methods. Our analysis revealed that the sperm ultraestructure of the leptodactylines was very similar to that of other anurans. The main differences occurred at the acrosomal complex region. Furthermore, we detected two distinct sperm morphotypes, one of them observed in all polyandrous species analyzed. Polyandrous Leptodactylus species produced larger sperm at higher densities and presented larger relative testes mass and seminiferous tubules compared to non polyandrous species. The correlated character evolution test showed that these gonad and sperm traits, all with values above the mean, correlated with the presence of polyandry in the genus. Thus, our results suggest that the sperm competition is an important selective pressure, leading to an increase in sperm size and density in Leptodactylus males, also increasing gonad mass allocation, probably as a way to increase fertilization success